EVOLVING RETAIL STRATEGIES IN THE JOHANNESBURG CENTRAL BUSINESS DISTRICT - Olitzki, Jonathan (My University, 2014)
The Johannesburg Central Business District, and the retail in it, has evolved dramatically during the course of its relatively short, but tumultuous history. Having begun with a few small shops serving the young mining town in the late 19th century, the CBD soon became the hub of retail activity for the city and the commercial heart of the country. By the end of the millennium, a combination of political, economic and social factors had resulted in the decline of the city centre and its retail sector. In an attempt to gentrify the CBD, the city’s stakeholders began to implement a variety of urban renewal strategies. Whilst the face and nature of the CBD had changed from what it once was, it began striving to become a “World Class African City”, rather than its previous contrived efforts at being a “European City in Africa.” As the renewal strategies started to gain traction, and the CBD began to stabilise, opportunities began presenting themselves for retailers. The CBD remains a hive of activity for a large population, more representative of the national demographic. An opportunity exists for retailers that are able to adapt to the prevailing nature of the CBD and its citizens. The research seeks to identify how retail has evolved in the Johannesburg CBD, in response to the various changes the city has undergone. Various literature sources dealing with the subject is discussed, and 20 retailers were interviewed to gain an insight into the effects that the decline of the city and the resulting renewal initiatives implemented, have had on the nature and dynamic of retail. The results are aggregated and discussed, with various suggestions presented as to how to the city’s stakeholders may best work together to improve the fortunes of both the city and the retail in it.
MBA thesis
Keywords: Retail industry; Retail districts